2016
DOI: 10.1177/0164027515606192
|View full text |Cite
|
Sign up to set email alerts
|

The Italian Version of the Tilburg Frailty Indicator

Abstract: This study aims to assess the reliability, construct validity (convergent/divergent), and criterion validity of the Italian version of the Tilburg Frailty Indicator (TFI). The TFI is a self-report questionnaire for screening frailty in older adults. Two hundred and sixty-seven community-dwelling older adults were involved. Psychometric properties were analyzed using validated instruments. Adverse outcomes such as disability, falls, and visits to a general practitioner were detected. Participants were mainly wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 37 publications
10
46
0
Order By: Relevance
“…The total TFI score and the average score of all subdimensions were statistically significantly higher in women than in men (p < 0.001). These results were similar to those of other validity-reliability studies of the TFI performed worldwide (17,20). In the original study, Gobbens et al developed the TFI with two groups: 245 and 234 people with average ages of 80.3 and 80.2 years with a total TFI score of 4.7/4.7, physical score of 2.6/2.5, psychological component score of 0.9/1.0, and social component score of 1.2/1.3 (13).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The total TFI score and the average score of all subdimensions were statistically significantly higher in women than in men (p < 0.001). These results were similar to those of other validity-reliability studies of the TFI performed worldwide (17,20). In the original study, Gobbens et al developed the TFI with two groups: 245 and 234 people with average ages of 80.3 and 80.2 years with a total TFI score of 4.7/4.7, physical score of 2.6/2.5, psychological component score of 0.9/1.0, and social component score of 1.2/1.3 (13).…”
Section: Discussionsupporting
confidence: 91%
“…The internal consistency for the total TFI score was at acceptable levels but the Cronbach's alpha reliability coefficient and adjusted item total correlations showed that the internal consistency reliability coefficients were low for some of the subitems of the TFI, particularly those of the social component. These results are similar to the results obtained for the original version of the TFI and other translated versions (5,13,20). CFA of the scale revealed that the RMSEA and SRMR values were <0.08 and that the CFI, GFI, and AGFI values were >0.90.…”
Section: Discussionsupporting
confidence: 86%
“…Our results confirm that the TUG time T is significantly correlated with the TFI, both total score TFIts and physical domain TFIpd [8]: r = 0.470 (p-value = 0.012), r = 0.473 (p-value = 0.011), respectively. More importantly we can notice that most of the proposed gait features correlates with the TFI as well.…”
Section: Gait Features and Frailty Assessmentsupporting
confidence: 81%
“…Most of the participants were female (83.3%) and the mean age was 75.6 ± 7.5 years. The participants were asked to fill the TFI questionnaire; in particular, in this study the total score of the TFI in addition to the 8 items of the TFI physical domain have been considered [8]. The TFI is a recognized instrument for frailty detection and can be used to unveil correlation between other objective features and the onset of the syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation